Point losing KPIs in final competitions of karate world championships - 2014 and 2016 - Alinaghipour, M.; Zareian, E. (International Journal of Sports Science, 2019)
Excelling in the performance of his or her chosen sport is the major aim of any elite athlete. The aim of this study was to understand and determine frequencies of point losing KPIs executed during Karate World 2016 final competitions among world-class karate athletes. There has not been any similar research in Karate KPIs yet. All the 20 final competitions of individual and team matches in World Championship 2014 and 2016 have been downloaded in HD quality. A group consisted of six skillful karate fighters was set to determine point losing KPIs. By the help of Kinovea video analysis software and Excel Microsoft Office 2013 the data of the matches has been recorded. A total number 390 point losing KPIs in the final competitions has been analyzed. The results indicate that "Point winner starts an attack" stands first with 44 out of 390, and the second most point losing KPI occurred when "Point loser starts an attack" with 37 out of 390. Furthermore, "Wrong technique selection" by fighters rated in the third place among point losing KPIs and is also an evidence of speed increase in today`s Karate competitions.